Exploring Intercultural Learning Experiences: A Phenomenological Study of Bilingual Elementary Teacher Education Students in Student Mobility Programmes to Taiwan, Philippines, and Thailand - Rachmadyanti, Putri (Pelopor Publikasi Akademika, 2025)
This study was motivated by the importance of cross-cultural learning experiences in strengthening the competencies of prospective primary school teachers in the global era. The purpose of this study was to explore the learning experiences of bilingual students in the Elementary Teacher Education Study (ETE) Programme who participated in off-campus learning programmes in three countries, namely Taiwan, the Philippines, and Thailand. A phenomenological approach was used to understand the meaning of students' learning experiences in different cultural and educational environments. Data were collected through in-depth interviews, observations, and analysis of relevant documents, then analysed using the Miles and Huberman model. Five bilingual students took part in this study through in-depth interviews and document analysis. The results showed that off-campus learning experiences had a significant impact on improving students' language skills, cultural adaptation abilities, and pedagogical understanding. Students also revealed that this experience broadened their knowledge of innovative learning methods, improved their cross-cultural communication skills, and strengthened their competencies as prospective educators. These findings have important implications for the development of curricula and educational policies that support cross-cultural learning for Elementary Teacher Education students.